Prediksi Jumlah Stunting Kabupaten Pamekasan Menggunakan Metode Statistical Parabolic - Iis Setiana; Luluk Sarifah (Alpha-Epsilon: Journal of Mathematics, 2026)
Indonesia is a country that is included in the target of high stunting management in the world, so stunting remains a problem that needs to be addressed. For example, the number of stunting in Pamekasan Regency. Currently, Pamekasan Regency is included in the target of stunting management with a stunting prevalence of 25.1% covering 21 health centers from 13 sub-districts. The purpose of this study is to predict the number of stunting in Pamekasan Regency in 2018-2024 using the statistical parabolic method. Statistical parabolic is one method that is able to make predictions based on past data, then in this study used data on the number of stunting in 2018-2024 obtained from the Pamekasan Regency Health Office. After calculating the predicted number of stunting in 2018-2024 based on the MAPE value obtained the result of 5.45%. Therefore, it can be concluded that the statistical parabolic method is good to be used to predict the number of stunting in 2025-2026.